COMPARATIVE ANALYSIS OF PUBLIC AND INDEPENDENT SCHOOL MANAGEMENT SYSTEMS IN SWEDEN (EDUCATION IN THE 21ST CENTURY, 2025)
In Sweden, alongside public schools, independent schools have expanded in recent decades, and today nearly 20% of compulsory school students attend independent schools. This article presents a comparative analysis of the management systems of public and independent schools in Sweden. It explores differences in governance, funding, school leadership, teacher recruitment, and academic outcomes. While both school types follow national standards, independent schools operate with greater autonomy and flexibility. The article highlights how school choice and governance structures contribute to educational segregation, despite comparable academic performance. The findings emphasize the need to balance autonomy, equity, and accountability in Sweden’s education system.
Keywords: Sweden; public schools; independent schools; management system; funding; school leadership; academic outcomes; educational segregation; autonomy; accountability; educational equity